Dynamic Analysis of Blasting Effect on Nanjung Tunnel Stability - Alio Jasipto; Nuhindro Priagung Widodo; Ganda Marihot Simangunsong; Simon Heru Prasesetyo; Made Astawa Rai; Dhika Noor Pradhana; Dimas Agung Saputra (PERHAPI, 2020)
This study aims to dynamically analyze blasting conducted in the Nanjung tunnel. Nanjung Tunnel is a twin tunnel that has a horseshoe-shaped section with each tunnel having a dimension of 10.2 m x 9.2 m, and 230 meters in length. The layers rock of this tunnel include silty clay, sandstone and dacite. Blasting was carried out on one of the tunnels consisting of dacite rock, having a 75-90% RQD and UCS 49-61 MPa. During the blast, PPV measurements were taken at several points around the tunnel using a minimate.Dynamic analysis is done by building a Nanjung Tunnel model on the RS2 software with the finite element method. Input data in this modeling is endeavored to approach actual conditions in the field, such as tunnel geometry, rock mass properties, and blasting plans carried out at STA 30-32 tunnels 2. This modeling is expected to produce PPV that is close to actual PPV and the results of this model will be continued to the stability analysis tunnel 1.Modeling results indicate that the tunnel 1 condition is stable during blasting. The stability of tunnel 1 based on smallest strength factor on the roof is around 2.6. Stability also seen from the strain level in dacite and sandstone rocks which are 0.07% and 0.38%. These strain levels are still permissible according to the Sakurai strain level diagram, 1983.